2017
DOI: 10.2147/dddt.s124324
|View full text |Cite
|
Sign up to set email alerts
|

Artonin E induces p53-independent G1 cell cycle arrest and apoptosis through ROS-mediated mitochondrial pathway and livin suppression in MCF-7 cells

Abstract: Artonin E is a prenylated flavonoid compound isolated from the stem bark of Artocarpus elasticus. This phytochemical has been previously reported to be drug-like with full compliance to Lipinski’s rule of five and good physicochemical properties when compared with 95% of orally available drugs. It has also been shown to possess unique medicinal properties that can be utilized in view of alleviating most human disease conditions. In this study, we investigated the cytotoxic mechanism of Artonin E in MCF-7 breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…Mitochondrial membrane permeabilization is one of the important key features of mitochondrial apoptotic pathway [ 18 ]. To measure the mitochondrial membrane potential, U-2OS and MG-63 cell lines were treated with DK1 and exposed to JC-1 dye; a compound that emits red fluorescence when present as aggregates, but fluoresces green when existing as monomers [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial membrane permeabilization is one of the important key features of mitochondrial apoptotic pathway [ 18 ]. To measure the mitochondrial membrane potential, U-2OS and MG-63 cell lines were treated with DK1 and exposed to JC-1 dye; a compound that emits red fluorescence when present as aggregates, but fluoresces green when existing as monomers [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The present study, thus, confirmed that ADP extract mediated cell cycle arrest at both S and G2/M phase in HCC cells followed by apoptosis through a TP53-independent pathway. Interestingly, in independent studies, Artonin E, a ruthenium- xanthoxylin complex and a novel analog of varacin C have been reported to induce apoptosis in target cancer cells via a TP53-independent pathway 47–49 . It would be our endeavor in future to evaluate and assess the anticancer activity of ADP-extract via alternative pathways of apoptosis induction in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the high level of p53 in patients with CML compared to the control patients. Moreover, the mitochondrial p53 gene is able to activate a pro-apoptotic protein that stimulates the release of cytochrome C causing potential apoptosis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%